2020
DOI: 10.1021/acscatal.0c02676
|View full text |Cite
|
Sign up to set email alerts
|

Fe(III)-Based Tandem Catalysis for Amidomethylative Multiple Substitution Reactions of α-Substituted Styrene Derivatives

Abstract: Developing tandem multiple C–H substitution reactions of simple alkenes provides rapid access to structurally complex unsaturated building blocks. Amidomethylative reactions that reserve CC double bonds have been composed sequentially for tandem catalytic substitutions around the CC bonds of alkenes. As a proof-of-concept demonstration, tandem catalytic amidomethylative processes, which effectively form multiple C–C bonds, have been developed to directly and selectively transform α-substituted styrenes into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Herein, we describe an air-stable tandem catalysis laboratory activity designed for organic II chemistry from the Cui research group. 24 Inside the homogeneous catalytic reactions of this laboratory activity are known mechanisms: iminium generation, imino-ene reaction, and aza-Prins reaction, which overlap with previously covered reactions. The experiment produces core structures in pharmaceutical molecules that combine α-methylstyrene with bis(tosylamido)methane using the Lewis acid iron triflate as the homogeneous catalyst.…”
Section: ■ Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Herein, we describe an air-stable tandem catalysis laboratory activity designed for organic II chemistry from the Cui research group. 24 Inside the homogeneous catalytic reactions of this laboratory activity are known mechanisms: iminium generation, imino-ene reaction, and aza-Prins reaction, which overlap with previously covered reactions. The experiment produces core structures in pharmaceutical molecules that combine α-methylstyrene with bis(tosylamido)methane using the Lewis acid iron triflate as the homogeneous catalyst.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Catalytic reactions can involve homogeneous or heterogeneous catalysts. Herein, we describe an air-stable tandem catalysis laboratory activity designed for organic II chemistry from the Cui research group . Inside the homogeneous catalytic reactions of this laboratory activity are known mechanisms: iminium generation, imino-ene reaction, and aza-Prins reaction, which overlap with previously covered reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work has adopted bis(tosylamido)methane (BTM), a bench-stable releaser for the labile tosylformaldimine, as an effective amidomethylating reagent for ruthenium(II)-catalyzed C-H amidomethylation reactions 23 and iron(III)-catalyzed tandem cyclization reactions with alkenes (Scheme 3). 24 While the freshly prepared tosylformaldimine was shown to be ineffective, BTM was rationalized to have a properly controlled rate of the release of the formaldimine, which may match the rates of the C-H amidomethylation process to enable the reaction. On the other hand, recently we have developed a practical synthesis of 1,2-ditosyl-1,2-diazetidine (DTD, Scheme 3, I).…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…Recently, inspired by the above [2 + 2 + 2] tandem cycloaddition reaction [30][31][32][33][34] catalytic pathway, Cui et al reported a tandem amidomethylative reaction catalyzed by Fe(III). 35 When multiple amidomethylation steps occurred through the elimination of the recovered C]C bonds, HHPs were directly synthesized from a-substituted styrene derivatives. As shown in Scheme 1, the yield of HHP (P) from the reaction of bis(tosylamido)methane (A) and a-phenylstyrene (B) is 69% (DCE ¼ 1,2dichloroethane, 70 C, 2 h).…”
Section: Introductionmentioning
confidence: 99%